Click-click, who’s there? Acoustically derived estimates of sperm whale size distribution off western Ireland - Barile, Cynthia; Berrow, Simon; O’Brien, Joanne (Frontiers in Marine Science, 2024)
Understanding the structure of populations is a critical element to the establishment of management and conservation measures. Sperm whales Physeter macrocephalus are characterised by a demographic spatial segregation, associated with a conspicuous sexual dimorphism reflected in their vocalisations. These characteristics make acoustic techniques very relevant to the study of sperm whale population structure, especially in remote, challenging environments. The reliability of using inter-pulse intervals of sperm whale clicks to infer body size has long been verified and extensively used. We provide the first size structure estimates of the sperm whale population in an area where assumptions on population structure mainly relied on sparse observations at sea, whaling records and stranding data. Over 10,000 hours of acoustic data collected using both static acoustic recorders and towed hydrophone arrays in Irish offshore waters were processed using a machine learning-based tool aimed at automatically extracting inter-pulse intervals from sperm whale recordings. Our analyses suggested that, unlike previously thought, large males would not account for the majority of the animals recorded in the area. We showed that adult females/juvenile males (length 9-12 m) were predominant, accounting for 49% (n = 788) of the number of individuals recorded (n = 1,595), while the proportions of immature individuals (length <9 m) and adult males (length >12 m) were well balanced, accounting for 25% (n = 394) and 26%(n = 413) of the recorded whales, respectively. Our data also suggested some size segregation may be occurring within the area, with smaller individuals to the south. The implications of such findings are crucial to the management of the population and provide an important baseline to monitor changes in population structure, particularly relevant under changing habitat conditions.